Reclamation and sedimentation impacts around the Wairuhu River estuary, Poka-Galala threshold - Noya, Yunita A.; Manuputty, Gratia (Universitas Malikussaleh, 2023)
Wairuhu River is disembogued on the sill of Poka-Galala, Ambon Bay. The estuary is affected by the coastal reclamation which led to the fester sedimentation. It triggers the problem of altering the shoreline and the dynamics of water movement, as well as the surrounding ecosystem. The modeling approach was applied to reconstruct the alterations around the estuary. The study aimed to estimate the changes on the shoreline, current patterns, and sediment transport patterns (suspended sediment), and to describe marine resources around the estuary of Wairuhu. MIKE 3 FM was utilized to reconstruct the pattern of flow and sediment transport changes, and coordinates plottings from satellite data were used to measure the coastline. The model was validated by using the data of tide and surface flow. The results showed the alteration pattern of the shoreline around the Wairuhu estuary occurred as a result of coastal reclamation. The flow validation (mooring and model) using RMSE was 0.38 which meant there was no difference between the model and mooring. By the model, the flow pattern that passed through the APG was following the tidal pattern. The changes in the tidal platform also occurred on the sediment transport pattern that formed the total distribution pattern of SSC (suspended sediment concentration). Several classes of macroflora and macrofauna were uncovered, such as Malacostraca, Echinoidea, Bivalvia, Asteroidea, Ophiuroidea, and Gastropoda.Keywords: Modeling; Poka-Galala sill; Sedimentation; Wairuhu River